Matriarchy through cultural change in Zainab Alkali`s the stillborn and the descendants - Muhammad, Usman Ambu; Mani, Manimangai; Talif, Rosli; Singh, Hardev Kaur Jujar (Center for Resource, Research and Publication Services, 2017)
Alkali’s society is deeply patriarchal in nature and women’s position does not go beyond a mere feeble and second class figure. In Northern Nigerian society, women have no say in whatever matters that may arise in the family. The men are the ones to decide, even if the matter affects the women. With this picture of Northern Nigerian society, Alkali has the boldness and courage to come up with questions on women’s role in her literary writings. In the novels, The Stillborn and The Descendants Alkali established matriarchal society through cultural change which means supporting and encouraging gender conflict to continue. The objective of this paper is to examine how cultural change in Alkali’s society is used in establishing matriarchal society using her female characters in the two texts. Textual analysis is to be conducted as the methodology, in order to discover how cultural change and female characters are used in establishing matriarchy. Nego-feminism is hoped to be the tool for bridging the gap created by Alkali in the two texts.